The choice of combination antihypertensive therapy in patients with type 2 diabetes - O. A. Koshelskaya; O. A. Zhuravleva; R. S. Karpov (Медицинский совет, 2015)
The article tells about optimum choice of combination antihypertensive therapy in patients with diabetes mellitus 2. The article discusses the efficacy of combination therapy based on two types of RAAS blockade (angiotensin-converting enzyme inhibitor or angiotensin II receptor antagonist) with indapamide retard and amlodipine, and the treatment regimen without RAAS blockers, which is based on the combination of dihydropyridine calcium channel blocker, indapamide retard and cardioselective beta blocker. The clinical experience with the three mentioned schemes of anti-hypertensive therapy is described; the benefits of combination of perindopril and amlodipine prior to valsartan and amlodipine or amlodipine and metoprolol succinate are demonstrated.